Sanctified by grace : a theology of the Christian life - Eilers, Kent; Strobel, Kyle, 1978- (London, Bloomsbury, 2014)
Books on the Christian life abound. Some focus on spirituality, others on practices, and others still on doctrines such as justification or forgiveness. Few offer an account of the Christian life that portrays redeemed Christian existence within the multifaceted and beautiful whole of the Christian confession. This book attempts to fill that gap. It provides a constructive, specifically theological interpretation of the Christian life according to the nature of God's grace. This means coordinating the Triune God, his reconciling, justifying, redemptive, restorative, and otherwise transformative action with those practices of the Christian life emerging from it. The doctrine of the Christian life developed here unifies doctrine and life, confession and practice within the divine economy of grace. Drawing together some of the most important theologians in the church today, Sanctified by Grace achieves what no other theological text offers -- a shared work of dogmatic theology oriented to redeemed Christian existence.
Introduction : The Christian life in dogmatic key / Kent Eilers and Kyle Strobel -- Part I. The Gracious One : -- The triune God
Includes bibliographical references and index.
Keywords: Grace (Theology); Christian life; Christian life; Grace (Theology)